Wasatiah in the Qur`an: Gadamer's Hermeneutical Analysis of Moderated Verses in Al-Mishbah's Tafsir - Fahrur Razi; Abdulfatah; Fitriani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research focuses on the understanding and application of the concept of wasatiah in the Qur'an, using Gadamer's hermeneutic method in Tafsir Al-Misbah. This research was conducted in literature, where the researcher analysed the tafsir work using Hans Georg Gadamer's hermeneutic analysis tool. The main findings of this analysis show that Tafsir Al-Misbah is not just an explanation of the text, but also a response to the social context and conflicts that occurred at that time. Through Gadamer's approach, researchers found that Shihab integrated the concept of wasatiah with various contextual dimensions, both from the Qur'anic text and from the surrounding social reality. The results of the analysis show that the concept of wasaṭiyyah expressed by Shihab reflects a fair, balanced and tolerant attitude in everyday life. This concept applies in various aspects of life, both in world affairs and the affairs of the hereafter. The importance of this research lies in the effort to understand and apply the concept of wasatiah in the context of an increasingly complex and turbulent life, especially in the face of the phenomenon of moral and mental decline in Islamic society.